'Am I damaging my own family?': Relational changes between foster carers and their birth children. (January 2016) - Thompson, Hayley; McPherson, Susan; Marsland, Louise
Foster placements are more likely to break down where the foster carers already have birth children. Studies that explore the impact of fostering on foster carers and their birth children have suggested that relational changes occur, but these changes have not been examined in depth. This study aimed to explore the impact of fostering on parent–child relationships within foster families. Nine foster carers (including three couples) were interviewed separately, and the data were analysed using constructivist grounded theory methods. Analysis indicated that birth children may attribute particular importance to their position in the family (e.g. oldest child, youngest child) and that this is a key element of the way in which they relate to their parents. Emotional security and parent–child relationships can therefore be strained by a foster placement not taking this into account. Foster children also introduce significant competition for parental resources, putting a strain on relationships. Foster carers seem to prioritise, consciously or not, the preservation of relationships within the biological family. Reflecting on relationships and making changes to maximise potential improvements in relationships can lead to positive outcomes, and this can have an impact on whether families continue fostering or not.